The Effectiveness of Witness and Victim Protection Institutions as Non-Structural Institutions - Kartikojati, Yulius; Markus, Dwi Pratiwi; Tuasikal, Hadi (Jurnal Hukum Replik, 2024)
Legal protection is an essential service mandated by the Constitution of the Republic of Indonesia, 1945. Article 28I, paragraph (4), underscores the state's responsibility for the protection, promotion, enforcement, and realization of human rights. In recognition of the importance of safeguarding the community, the Witness and Victim Protection Institution was established under Law Number 31 of 2014 and further defined in Presidential Regulation Number 60 of 2016. The institution’s mandate encompasses all stages of the criminal justice process, ensuring that witnesses and victims feel safe when providing testimony. This research employs a normative methodology, involving a review of library documents to analyze legal texts in accordance with applicable principles and standards. The findings indicate that while the Witness and Victim Protection Institution has made significant achievements in protecting witnesses and victims in severe cases, its effectiveness as a non-structural institution remains questionable. This is attributed to a lack of regulations governing its management, staffing, oversight, and transparency. To enhance the institution's effectiveness, it is essential to improve regulatory frameworks, increase public awareness, and strengthen its capacity. With these improvements, the Witness and Victim Protection Institution is expected to play a more pivotal role in safeguarding the rights of witnesses and victims, supporting equitable law enforcement, and protecting human rights within Indonesia's criminal justice system.Keywords: Effectiveness, Legal Protection, Witness and Victim Protection Institutions, Non-Structural Institutions